(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
The characteristics of the profession drivers, in the nature of their work, influence the occurrence of various health risk factors. Professional drivers are, in general, exposed to a workspace that is limited, vibrations, uncomfortable seats and forced position meanwhile prolonged sitting. The objective of our study was to investigate psychosocial risk factors among Slovene professional drivers’ samples in a cross-sectional study. The data collection was performed by the use of a survey questionnaire, which was distributed among professional drivers. The research was conducted on 259 professional drivers; 125 train drivers, 57 bus drivers, 57 truck drivers and 20 other drivers (eg. taxi drives). The cooperation in the survey was anonymous and voluntary. The measurement for coping with psychosocial risks and absenteeism – OPSA was used, which is divided into two parts 1) a general part (which includes sociodemographic and health related information about the employees as well as 2) the part that focuses on employee psychosocial load evaluation. With the use of analysis of variance, we tested wheatear there were statistically significant differences in OPSA statements among mentioned groups of drivers. There is no evidence that the psychosocial risk factors (OPSA profile) are statistically significantly different between specific groups of drivers. However, could be noted that bus and train drivers are the most vulnerability occupational groups among professional drivers. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.